GROWTH PERFORMANCE, SURVIVAL RATE, AND RESISTANCE AGAINST AHPND OF Litopenaeus vannamei JUVENILES FED WITH SYNBIOTIC BIO-ENCAPSULATED ARTEMIA - Yudiati, Ervia; Azhar, Nuril (Jurnal Riset Akuakultur, 2024)
The whiteleg shrimp (Litopenaeus vannamei) is a highly valued aquaculture species globally, yet its production faces challenges due to disease outbreaks, notably acute hepatopancreatic necrosis disease (AHPND). This study aimed to evaluate the growth and survival of L. vannamei juveniles fed with synbiotic bio-encapsulated Artemia and their resilience against AHPND-causing Vibrio parahaemolyticus and salinity stress. The experiment employed a completely randomized design with two treatments: one with synbiotic-enriched Artemia (600 ppm alginate and Lactobacillus bulgaricus) and a control without synbiotic. Each treatment was replicated five times, using 600 juveniles at a density of 30 post-larvae per L over a 14-day rearing period. Growth and survival metrics were recorded, followed by challenge tests for AHPND and salinity shock. The juveniles' survival rate was recorded 54 hours post-infection with VpAHPND and every 10 minutes for 230 minutes after salinity exposure until 100% mortality. Results indicated higher survival (92.0 ± 9%), length gain (243.33 ± 18.80 mm), specific growth rate (18.44±2.01%), and stress tolerance in juveniles fed synbiotic encapsulated Artemia compared to the control. The survival rates for the challenge test with AHPND and salinity shock were similarly improved under synbiotic treatment, suggesting that synbiotics significantly benefit nursery production of L. vannamei. This study highlights the potential of synbiotic application in enhancing the resilience and growth of L. vannamei against common stressors in aquaculture, indicating its potential to support more sustainable shrimp farming practices.Udang vaname (Litopenaeus vannamei) adalah komoditas budidaya bernilai tinggi di seluruh dunia, namun produksinya menghadapi tantangan akibat wabah penyakit, terutama serangan acute hepatopancreatic necrosis disease (AHPND). Penelitian ini bertujuan untuk mengevaluasi pertumbuhan dan kelangsungan hidup benih L. vannamei yang diberi pakan Artemia yang dibioenkapsulasi dengan sinbiotik serta ketahanannya terhadap Vibrio parahaemolyticus penyebab AHPND dan stres salinitas. Eksperimen ini menggunakan rancangan acak lengkap dengan dua perlakuan: satu dengan Artemia diperkaya sinbiotik (600 ppm alginat dan Lactobacillus bulgaricus) dan kontrol tanpa sinbiotik. Setiap perlakuan diulang lima kali, dengan menggunakan 600 ekor benih udang pada kepadatan 30 ekor pascalarva per L selama 14 hari periode pemeliharaan. Parameter pertumbuhan dan kelangsungan hidup dicatat, diikuti dengan uji tantang terhadap AHPND dan kejutan salinitas. Tingkat kelangsungan hidup benih dicatat 54 jam pasca-infeksi dengan VpAHPND dan setiap 10 menit selama 230 menit setelah paparan salinitas hingga mortalitas mencapai 100%. Hasil menunjukkan kelangsungan hidup yang lebih tinggi (92,0 ± 9%), peningkatan panjang (243,33 ± 18,80 mm), laju pertumbuhan spesifik (18,44 ± 2,01%), dan toleransi stres yang lebih baik pada benih udang yang diberi pakan Artemia berenkapsulasi sinbiotik dibanding kontrol. Tingkat kelangsungan hidup pada uji tantang dengan AHPND dan kejutan salinitas juga meningkat dengan perlakuan sinbiotik, menunjukkan bahwa sinbiotik memberikan manfaat signifikan pada produksi L. vannamei fase pendederan. Penelitian ini menunjukkan adanya potensi aplikasi sinbiotik dalam meningkatkan ketahanan dan pertumbuhan L. vannamei terhadap stresor umum dalam akuakultur, serta potensinya untuk mendukung kegiatan budidaya udang yang lebih berkelanjutan.